Раскопки полковника Манро на Гераклейском полуострове во время Крымской войны 1854-56 годов - Аржанов, А. Ю. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary A. Arzhanov. Colonel Munro Excavations at Heraklean Peninsula During the Crimean War, 1854–56 Years This article describes the excavation of an English officer of the 39th Infantry Regiment, Lieutenant-Colonel William Munro at Sevastopol during the Crimean War of 1854–55 years. Based on military plans and memoirs of those years, the author determines the exact location of the excavation near English Army headquarters. Also, this place gets geo-referenced in relation to modern place-named of Sevastopol. Exploring the newspaper illustrations and observing the eyewitnesses, concluded about the nature of the investigated structures — a Chersonesos farm with winery that existed in Hellenistic time. Later there is cilcular building, overlapping the winery. Also the author analyzes a collection of finds, donated by Colonel Munro to the British museum. Based on the expert opinion of the British museum, concludes the lifetime farmhouse. According to the author, this farmhouse just existed between the III BC on II—III C. Key words: Sevastopol, Crimean War, Chora of Chersonesos, Colonel Munro, excavations.